An Investigation into The Challenges of Writing Research Project at The Departments of English in Iraqi Kurdistan Region Universities from The Students’ Perception - Mahmood Kareem, Shano; Sattar Abdulrahman, Barham (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The present study aims to investigate the challenges Kurdish senior EFL students face while writing graduation research projects at the departments of English in Iraqi Kurdistan Region universities. The study hypothesizes that the majority of Kurdish EFL undergraduates face challenges while writing their research projects and the challenges could be related to lack of knowledge on paraphrasing, plagiarism, referencing, citation, research design, lack of practice, and poor supervision. To investigate the study hypothesis, the researcher designs a 29-item questionnaire which is distributed among 218 senior students of Department of English, College of Basic Education at four different Iraqi Kurdistan Region universities, namely University of Sulaimani, Salahaddin University-Erbil, University of Halabja, and University of Duhok during the academic year 2021-2022. The collected data is statistically analyzed using SPSS version 24 focusing on frequency, percentage, standard deviation, relevant importance, and level. The study concludes that the majority of problems the students face during writing the research projects is related to a lack of interest in research, experience and practice, good knowledge of the methodology, and positive and effective feedback. Finally, it recommends EFL instructors/supervisors to provide the students with feedback and opportunity to practice, guide them avoiding plagiarism, and teach them academic writing.